CHEMICAL, NUTRITIONAL AND SENSORY CHARACTERIZATION OF SWEET POTATO SUBMITTED TO DIFFERENT COOKING METHODS - Ogliari, Regiane; Soares, Jaqueline Machado; Teixeira, Flávia; Schwarz, Kélin; da Silva, Kátia Aparecida; Schiessel, Dalton Luiz; Novello, Daiana (International Journal of Research -GRANTHAALAYAH, 2020)
The objective was to evaluate different cooking methods effect on chemical, nutritional and sensory characteristics of sweet potatoes. Samples were subjected to four cooking methods: boiled in water, fried, microwaved and baked. In general, pH, Titratable Acidity and Soluble Solids contents were altered by cooking methods. Reducing, Non-Reducing and Total Sugars levels increased after cooking, regardless of the method used. Levels of red and yellow were lower in tubers after the methods of boiled and baked, while the light reduced in all cooking processes. Cooking by boiled and fried increased Total Carotenoid content, reducing it in other methods. Except for boiled, all other processes increased Phenolic Compounds content. Ascorbic Acid content increased in all cooking processes, being higher for fried. Sweet potatoes cooked by boiled had higher moisture content and lower protein, lipid, carbohydrate and energy, while fried was the process that most elevated the content of these nutrients. Sensory scores were higher for sweet potatoes cooked in fried method. It is concluded that the processes of baked, boiled, fried and cooking in microwave alter chemical and nutritional characteristics of sweet potatoes. The tuber submitted to fried has greater sensory acceptability, however it is the least suitable for consumption due to high levels of fat and energy.